Laparoscopic Primary repair of Common Bile Duct: Does the Suture Size Matter? - Joshi, M R; Sharma, S K (Journal of Nepal Health Research Council, 2011)
Background: Laparoscopic common bile duct exploration and primary closure is being popular method of management for common bile duct stone. As the standard method of procedure is yet to be established, we have compared the outcome of using different size suture for the closure of choledochotomy wound. Methods: Prospective cross-sectional study was conducted where patients were categorized in two groups. Those with 3-0 suture were grouped â€œAâ€ and those with 5-0 inâ€œBâ€. Outcome regarding the suturing time, cost, postoperative bile leak and hospital stay were compared between two groups. Results: Total 42 cases were included, twenty-one in. Mean age in group A is 38.6yrs and in group B is 44.24yrs. The sex ratio is comparable. Mean time taken for suturing is almost same (34.4 mins Vs 32.6 mins). The Post-operative bile leak is significantly for shorter duration in 5-0 group than 3-0 group. But there is no difference in overall hospital stay. Conclusions: Post-operative bile leak is significantly less when common bile duct is sutured with thinner needle and suture. This does not increase the cost, does not prolong the operating time and is not associated with other complications. Although the overall hospital stay is same. Further large scale study is needed. Keywords: bile, choledocholithisis, laparoscopiccholedocholithotomy, suture